THE CHALLENGES FACED BY ENGLISH TEACHERS AT VOCATIONAL HIGH SCHOOLS IN KARANGLEWAS IN IMPLEMENTING MERDEKA CURRICULUM AND RELEVANT SOLUTIONS - Toyibah, Ummi Anisatul; Wulandari, Yasinta; Aniuranti, Asfi (Economics, Social, and Humanities Journal (Esochum), 2024)
This research is aimed to find out the English teachers’ challenges in implementing Merdeka Curriculum at vocational high schools and the solutions or ways the teachers addressed those challenges. This research used descriptive qualitative research method. The subjects of this research were two English teachers from two vocational high schools in Karanglewas District. The techniques for collecting the data of this research were interview, observation, and documentation. In analyzing the data, the researcher used three steps called data reduction, data display, and conclusions. The results of the study showed that English teachers at Karanglewas Vocational Schools have challenges in implementing Merdeka Curriculum. The challenges were categorized into two, they were internal challenges which originated from the teachers themselves, and external challenges which originated from students, government, and learning or school facilities. The internal challenges were teachers’ ability in using ICT tools, teachers’ capability in determining methods, and adjusting the time allocation and learning activities. While the external challenges were related to practical curriculum given by the government, students’ ability and skills, inadequate learning facilities and resources, and the school proximity to the railways. The results of this study also describe solutions that teachers have taken to overcome these challenges, such as learning by doing, using exciting learning method, motivating students, keeping students focused in learning, conducting listening session with an audio speaker in classroom, and providing e-books as students’ handbook.